Increased Risk of Group B Streptococcus Invasive Infection in HIV-Exposed but Uninfected Infants: A Review of the Evidence and Possible Mechanisms - Dauby, Nicolas; Chamekh, Mustapha; Melin, Pierrette; Slogrove, Amy L.; Goetghebuer, Tessa (Frontiers in Immunology, 2016)
Group B streptococcus (GBS) is a major cause of neonatal sepsis and mortality worldwide. Studies from both developed and developing countries have shown that HIV exposed but uninfected (HEU) infants are at increased risk of infectious morbidity, as compared to HIV unexposed uninfected infants (HUU). A higher susceptibility to GBS infections has been reported in HEU infants, particularly late-onset diseases (LOD) and more severe manifestations of GBS diseases. We review here the possible explanations for increased susceptibility to GBS infection. Maternal GBS colonization during pregnancy is a major risk factor for early-onset GBS invasive disease but colonization rates are not higher in HIV-infected compared to HIV-uninfected pregnant women, while selective colonization with more virulent strains in HIV-infected women is suggested in some studies. Lower serotype specific GBS maternal antibody transfer and quantitative and qualitative defects of innate immune responses in HEU infants may play a role in the increased risk of GBS invasive disease. The impact of maternal antiretroviral treatment and its consequences on immune activation in HEU newborns is important to study. Maternal immunization presents a promising intervention to reduce GBS burden in the growing HEU population.